Single Setting ERCP and Laparoscopic Cholecystectomy is a Safe Procedure in Patients with Cholecysto-Choledocholithiasis: A Prospective Study in a Peripheral-Level Hospital (Nepal Medical College Journal, 2020)
The ideal management of cholecysto-choledocholithiasis is an open cholecystectomy (OC) with the common bile duct (CBD) exploration worldwide. The single setting 2-stage approach- endoscopic retrograde cholangiopancreatography (ERCP), endoscopic sphincterotomy (EST), and CBD clearance followed by laparoscopic cholecystectomy (LC) offers an advantage, mainly by reducing the hospital stay, the cost, and the morbidity. The Objective of the study is to compare the ERCP+LC single setting approach with an OC+CBD exploration for the treatment of cholecysto-choledocholithiasis. This is an interim analysis of 160 patients with 83 (51.9%) patients in ERCP+LC and 77 (48.1%) in an open procedure (OC+CBD exploration) group respectively. We did a prospective study in patients admitted for the management of the cholecysto-choledocholithiasis in the Department of Surgery at the Lumbini Medical College and Teaching Hospital from November 2012–October 2015. They underwent 2-stage ERCP+LC in a single setting and we compared them with 2-stage OC+CBD exploration in a single setting approach. The patients with the open procedure were our control group. All the included cases in the study were elective. The procedure was feasible in our hospital. Similarly, the hospital stay was significantly shorter in the ERCP+LC group; 3.92±0.719 days vs 10.30±1.557 days, p